Strong intramolecular hydrogen bonding in protonated β-methylaminoalanine: A vibrational spectroscopic and computational study. Issue 1 (February 2019) - Linford, Bryan D; Le Donne, Andrea; Scuderi, Debora; Bodo, Enrico; Fridgen, Travis D
The gas-phase structure of protonated β-methylaminoalanine was investigated using infrared multiple photon dissociation spectroscopy in the C–H, N–H, O–H stretching region (2700–3800 cm −1 ) and the fingerprint region (1000–1900 cm −1 ). Calculations using density functional theory methods show that the lowest energy structures prefer protonation of the secondary amine. Formation of hydrogen bonds between the primary and secondary amine, and the secondary amine and carboxylic oxygen further stabilize the lowest energy structure. The infrared spectrum of the lowest energy structure originating with harmonic density functional theory has features that generally match the positions of the experimental spectra; however, the overall agreement with the experimental spectrum is poor. Molecular dynamics calculations were used to generate a gas-phase infrared spectrum. With these calculations a reasonable match with the experimental spectrum, especially in the high-energy region, was obtained. The results of the molecular dynamics simulation support the density functional theory calculations, with protonation of the secondary amine and the formation of a hydrogen bond between the protonated secondary amine and the primary amine. This work shows the importance of accounting for anharmonic effects in systems with very strong intramolecular hydrogen bonding.